Child and Childhood in Charles Dickens´s novels - Dvořáková, Romana (Univerzita Pardubice, 2008)
The work focuses on the depiction of Victorian childhood in novels of Charles Dickens. The two novels used as primary sources are Oliver Twist and David Copperfield. The work is based on a text analysis of the primary sources and their comparison with information in secondary sources. The aim of the work is to prove that Charles Dickens described the Victorian childhood in a realistic way in his novels.
Obraz dětství v románech Charlese Dickense
Keywords: viktoriánské období; dítě; dětství; Victorian period; Oliver Twist; David Copperfield; child; childhood